Board attributes and sustainability reporting quality in family firms: Empirical evidence from Malaysia - Ghuslan, Mohamad Iruwan; Mahmud, Nurfarizan Mazhani; Rosli, Siti Aisyah; Ahmad Yahya, Naimah; Che Hasan, Haslinawati (International Journal of Accounting, Finance and Business, 2025)
This study aims to examine the effect of board attributes on sustainability reporting quality in family firms. This study was conducted on a sample of 233 family firms listed on Bursa Malaysia from 2017 to 2018 using OLS regression. Results suggested that board independence and female directors are positively linked with the sustainability reporting quality (SRQ). This implies that these board attributes have positive influence to enhance the quality of sustainability reporting of Malaysian family firms. However, this study demonstrated that board education level and board education background have no significant impact on SRQ. The results indicated that boards with diverse education background and level are not influential to improve the sustainability reporting decisions of firms in the presence of concentrated family ownership. The current study fills the literature void by providing additional evidence on the impact of board attributes, focusing on board characteristics and board diversity on SRQ in Malaysian perspective. The findings assist regulators and policy makers to better understand the impact of corporate governance practices on SRQ, primarily on family firms as family firms dominate about 70 percent of listed firms in Bursa Malaysia. The findings also benefit practitioners and corporate management by providing guidelines and valuable input to better manage their sustainability reporting quality as recommended by MCCG guidelines.